2016
DOI: 10.1080/15627020.2016.1261002
|View full text |Cite
|
Sign up to set email alerts
|

Stress steroid levels and the short-term impact of routine dehorning in female southern white rhinoceroses (Ceratotherium simum simum)

Abstract: Rhinoceros populations in Africa are under severe threat as a result of surging poaching rates and risk-mitigation strategies are continuously adapted in an attempt to ensure the survival of the species. This study compares faecal glucocorticoid metabolite (fGCM) levels of two age classes of limited free-ranging female white rhinos with fGCM levels of adult free-ranging female white rhinos. Subsequently, fGCM alterations in the limited free-ranging animals were monitored following routine dehorning as a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 16 publications
5
23
1
Order By: Relevance
“…This pattern matches findings in female South African Lesser Galagos (Galago moholi Smith, 1836; Scheun 2015) and female white rhinoceros (Ceratotherium simum simum Burchell, 1817;Badenhorst et al 2016) that demonstrate a potential link between alterations in pregnancyrelated progestagen and fGCM concentrations.…”
Section: Discussionsupporting
confidence: 81%
“…This pattern matches findings in female South African Lesser Galagos (Galago moholi Smith, 1836; Scheun 2015) and female white rhinoceros (Ceratotherium simum simum Burchell, 1817;Badenhorst et al 2016) that demonstrate a potential link between alterations in pregnancyrelated progestagen and fGCM concentrations.…”
Section: Discussionsupporting
confidence: 81%
“…The lack of a short-term hormone response to immobilization and dehorning runs counter to the trend observed by Badenhorst et al (2016) whereby rhinos underwent a spike in FCM concentrations immediately after their dehorning, experiencing an acute endocrine stress response. The differences between the two studies may be explained by variation in the timings of sample collection.…”
Section: Discussionmentioning
confidence: 62%
“…The differences between the two studies may be explained by variation in the timings of sample collection. Badenhorst et al (2016) reported a peak in FCMs 24–48 hours after dehorning, which rose to a median 32% (range: −7.0 to 293%) above the baseline, whereas by 72–86 hours after the event FCMs had decreased by a median of 16% (range: −24 to 42%) above the pre-dehorning baseline. In comparison, the samples in this study were collected a mean 80 hours (range: 24–166 hours) after dehorning and had declined a median 17.2% (range: −60 to 43%) below the pre-dehorning concentration.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations